Research in Cryptology Second Western European Workshop, WEWoRC 2007, Bochum, Germany, July 4-6, 2007, Revised Selected Papers - Lucks, Stefan; Sadeghi, Ahmad-Reza; Wolf, Christopher (Security and Cryptology ;, 2008)
This book constitutes the refereed proceedings of the Second Western European Workshop on Research in Cryptology, WEWoRC 2007, held in Bochum, Germany, in July 2007 The 12 revised full papers were carefully reviewed and selected from a total of 36 submissions. The papers cover topics such as foundations of cryptology, secret-key cryptosystems and hash functions, public-key cryptosystems, cryptographic protocols, implementation of cryptosystems and their integration into secure systems, secure operating systems and trusted computing, applications such as watermarking and code obfuscation.